Electrochemical and electrocatalytic properties of iron(II) and cobalt(II) phthalocyanine complexes integrated with multi-walled carbon nanotubes - Ozoemena, Kenneth I. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.